Diabetic patient presented with tingling and burning limbs- is this always peripheral neuropathy? - Siddiqui, Md Mahmudur Rahman; Asif, Dewan Shamsul (Bangladesh Journal of Medicine, 2019)
Abstract not available Bangladesh J Medicine July 2019; 30(2) : 108